2000
DOI: 10.2118/00-11-01
|View full text |Cite
|
Sign up to set email alerts
|

Application of Heat Treatment to Enhance Permeability in Tight Gas Reservoirs

Abstract: During the drilling and completion phases, the primary mechanisms of near-wellbore formation damage can be attributed to the following factors:pore throat constriction caused by clay swelling, deflocculating due to incompatible fluids or clay migration;water blocking resulting in a reduction in relative permeability to hydrocarbons;plugging with drill solids and mud products; andloading of the reservoir with drilling or completion fluids. In tight reservoirs, phase trapping and water-blocking are believed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The combustion and pyrolysis can remove organic matter and decompose minerals from shale and further increase shale matrix permeability [4,6]. Jamaluddin et al [12] confirmed an increment in permeability from 50% to 675% depending on the core type and treatment temperatures. The maximum temperature increment could reach around 650 • C. Gas-phase combustion for tight gas reservoirs may be an alternative for FHT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combustion and pyrolysis can remove organic matter and decompose minerals from shale and further increase shale matrix permeability [4,6]. Jamaluddin et al [12] confirmed an increment in permeability from 50% to 675% depending on the core type and treatment temperatures. The maximum temperature increment could reach around 650 • C. Gas-phase combustion for tight gas reservoirs may be an alternative for FHT.…”
Section: Introductionmentioning
confidence: 99%
“…Formation heat treatment (FHT) is a process with great potential in enhancing gas production from unconventional oil/gas reservoirs [1,[12][13][14]. Different heating technologies, such as an electrical heater, hot water flooding, high-temperature steam, in-situ combustion, and electromagnetic heating (microwave/radio frequency) and so on, were applied to the oil and gas industry [4,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the water in pores would be removed perfectly, due to the evaporation or dehydration of water at high temperature. Therefore, formation damage like water blocking could be prevented, and permeability of rock is enhanced by removing water in gas flow channel [9][10][11]. On the other hand, induced fracture generates, preexisting fracture propagates, and finally various kinds of fractures connect to be network under the action of thermal stress at high temperature [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, systematic studies on heat treatment are still rare and the application on stimulation of tight gas formation is urgent to understand. The previous studies on formation heat treatment are based on sandstone, and samples' permeability is relatively high [8,9,15,17]. Also, thermal cracking in rock, which has been studied a lot in nuclear waste storage, mining technique, HDR geothermal extraction, and stability analysis of constructions, is mostly based on granite that is not the natural gas reservoir [13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%